Wind-generated seed shadow in Southern Brazil: The influence of the mother plant and wind direction - Genz, Leone; Kissmann, Camila [UNESP] (FapUNIFESP (SciELO), 2020)
Diaspore dispersal is an essential function of plant species, with effects on plant populations and natural forest dynamics. This study examines how traits of the mother plant (height, crown spread and distance from the diaspores) and the wind (wind speed) affect the spatial distribution of anemochorous diaspores of Apuleia leiocarpa, Peltophorum dubium, and Jacaranda micrantha in Southern Brazil. The number of diaspores from A. leiocarpa, P. dubium, and J. micrantha decrease with the increase in distance from the mother plant and there was no influence of wind direction on the spatial distribution of diaspores. Diaspore sizes of these plants were not related to their dispersal distances. Diaspore dispersal for A. leiocarpa was negatively correlated to the plant height and the crown spread. The dispersal of Peltophorum dubium and Jacaranda micrantha were not influenced by the diaspores and plants traits considered in this study.
Keywords: Biodiversity conservation; Brazilian atlantic forest; Dispersal syndrome; Spatial distribution of diaspores